Enhancing the Workforce for Industry 5.0 - Susan Tee Suan CHIN (Communications of International Proceedings, 2021)
Contrary to the trends in Industry 4.0 toward technology and dehumanization, technological advancement and innovation best practices. Industry 5.0 will bend back toward the service of humanity. At workplaces, this industrial revolution will place greater importance on human intelligence than ever. The fifth industrial revolution brings in massive advantages, providing the candidates with a more personalized experience in their job search. Industry 5.0 recognizes the power of industry to achieve societal goals beyond jobs and growth to become a resilient provider of prosperity by making production respect the boundaries of our planet and placing the well-being of the industry worker at the center of the production process. The purpose of this study is to examine the soft skills required for Industry 5.0.
Keywords: Performance; Competitive Advantage; Sustainability; Future; Profits.